Factors That Affect A College Student's In-Game Purchase in Batam City - Valentino Chen; Farhan Alwie Rasyidhy; Lip Son; Leo Fransisco; Rainal Agus Setiawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Game is a media that is played with the aim of entertaining, relieving stress, filling time, even exercising and making money. One of the ways games make money is through in-game purchases or microtransactions, which have become commonplace among players and are found in many types of games nowadays. Although the Covid-19 pandemic has had a negative impact on the economy in Indonesia, this has not stopped Indonesians from spending money to buy in-game items. Therefore, this study aims to investigate the factors that encourage someone to make an in-game purchase in Batam. The research will be carried out quantitatively by distributing online surveys and having 385 respondents. The method of analysis that will be carried out is using SPSS and AMOS with SEM analysis. From the results of this study, it can be observed that monetary value, enjoyment value, and social value affect purchase intention positively. Therefore, a conclusion can be made that by paying attention to these factors, a student can be encouraged to spend in-game.